(untitled) (Bangladesh Journal of Botany, 2015)
Effects of Ginkgo biloba L. extract on the seed germination, seedling growth and leaf anatomy of barley under saline conditions were studied. In parallel with concentration rise, salt stress inhibited the seed germination and seedling growth of barley. The inhibitive effect of salt on the germination and coleoptile percentage was alleviated in varying degrees, and dramatically, by Ginkgo biloba application. However, it became ineffective in alleviating of salt inhibition on the radicle, coleoptile length, radicle number and fresh weight of barley seedlings. On the other hand, it was observed that Ginkgo biloba extract affected in different degrees the various parameters of leaf anatomy of barley seedlings, and this difference was statistically important. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22733 Bangladesh J. Bot. 44(1): 117-123, 2015 (March)